Produção e caracterização de hidromel utilizando a borra e resíduos do café processado por via úmida - Oliveira, Alberto Lima de (2020)
Containing high levels of fermentable sugars and phenolic compounds, the coffee husk and pulp are residues generated during the wet processing of coffee. As the world's largest coffee producer, Brazil generates tons of husk and pulp each year. In addition to these residues, the sludge resulting from the consumption of coffee has been the subject of studies in order to recycling it and how to better deposit it in the environment. Among the recycling forms, fermentative processes stand out, such as the production of mead. Mead is a fermented beverage obtained by diluting honey in water, with or without addition of nutrients and selected inoculum. The objective of this work was to evaluate the feasibility of using coffee sludge, husk and pulp in the production of mead. An extract of the husk and pulp containing 7 ºBRIX was obtained by crushing, pressing and filtering these residues, being used in the dilution of honey. Another treatment was carried out with a solution containing 15% sludge. For the control, honey diluted in sterile distilled water was used. Adulteration tests were performed on the honey used, obtaining negative results for Fiehe, Lugol and Lund's reaction. The yeast S. Bayanus Red Star Champagne and S. cerevisiae Lalvin EC 1118 were used as inoculum. Fermentations were started at 20 ºBRIX, pH 5.0 and 108 viable cells at a temperature of 20 ºC for the entire process. The stabilization of the consumption of reducing sugars, pH and CO2 release occurred after 240 hours. Fermentative kinetics was studied, obtaining higher values of fermentative efficiency (Fe), ethanol productivity (Qp) and conversion of the substrate into ethanol (Yp/s) for the medium added to the extract. The addition of the extract also increased cell viability during fermentation, being verified by a Neubauer Chamber with methylene blue reagent. The addition of coffee sludge increased the lag phase of the yeasts possibly due to presence of HMF, requiring a longer period to stabilize the levels of reducing sugars and pH. Meads were characterized as current legislation and among the parameters analyzed only the total acidity was outside the established standard, with the E Red treatment being the highest total acidity (48.70 meq.L-1). Meads were also characterized as content of phenolic compounds and antioxidant activity by the DPPH and ABTS methods. The Red Star Champagne strain stood out for the production of mead with higher alcohol levels and higher Fe values, which medium fermented by this yeast with the addition of the extract had higher alcohol content (13.88%). In general, the beverages produced by the EC 1118 strain showed higher levels of phenolic compounds and antioxidant activity. There was a variation in total phenolics from 332.30 (E Lalvin) to 268.33 GAE.L-1 (C Red). The E Lalvin treatment also showed greater antioxidant activity, with 2.50 TEAC mM.L-1 (ABTS) and 2.71 TEAC mM.L-1 (DPPH). The potential of husk and pulp extract in the production of mead is evident, since the addition of the extract to the wort resulted in drinks with higher alcohol content, higher concentration of phenolic compounds and antioxidant activity.